Association of vitamin A supplementation with immune-related allergic diseases: A meta-analysis - Su, Jingqiu; Li, Tian; Pan, Hua (Frontiers in Nutrition, 2022)
Background: Allergic diseases are type I hypersensitivity reactions mediated by various allergens. The most common allergic diseases include allergic rhinitis, allergic asthma, allergic dermatitis, and allergic conjunctivitis. The incidence of allergic diseases has been increasing in the recent past, and allergen avoidance and adoption of desensitization treatment can significantly decrease the incidence of allergic diseases. Previous studies have explored the association between vitamin A supplementation and allergic diseases; however, the results are inconsistency. The aim of the present study was to evaluate the association between vitamin A supplementation and allergic diseases, with a focus on atopy and wheezing. Methods: Articles reporting randomized controlled trials (RCTs) on the association of vitamin A supplementation and allergic diseases were retrieved from PubMed, Embase, Web of science, and China National Knowledge Infrastructure database from inception of to November 15, 2021. STATA 12.0 software was used for meta-analysis, sensitivity analysis and analysis of publication bias. Results: Seven studies comprising 2201 participants met the inclusion criteria and were included in the meta-analysis. The findings showed that vitamin A supplementation was associated with increased risk of atopy in young females compared with the placebo (RR = 1.70, 95% confidence interval [1.20, 2.41], P = 0.171, I2= 43.4% fixed effect model). The frequency of delayed atopy among adults was associated with vitamin A supplementation (MD = 0.46, 95% CI= 0.04, 0.88). Analysis showed no significant association between vitamin A supplementation with incidence of wheezing in children (RR = 1.40, 95% CI [0.49, 3.98], P = 0.018, I2= 82.1% random effect model). Sensitivity and publication bias analysis showed that each individual study did not affect the combined results and there was no significant publication bias among the studies. Conclusion: The findings showed that vitamin A supplementation is associated with increased risk of atopy but no correlation was observed with the incidence of wheezing. The results of this meta-analysis provide evidence for effective management of fibrosis. More studies should be conducted to verify the results.